Adsorption-Desorption Processes in Adsorption Chillers (Agricultural Engineering, 2016)
The aim of this paper is to present the adsorption chillers technology. The operating principle of these systems, the adsorbent-adsorbate pairs that are frequently applied and the enhancement techniques that allow improvement of their efficiency are presented. Analysis of the mass transfer and principles of mathematical modeling of such systems are also discussed. In the further part of the text, the results of experimental studies and comparison of these results with calculations based on the mathematical model of adsorption were presented.